2015
DOI: 10.3109/02713683.2015.1037924
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Axonal Transport and Glaucoma

Abstract: Glaucoma is increasingly recognized as a neurodegenerative disorder, characterized by the accelerated loss of retinal ganglion cells (RGCs) and their axons. Impaired axonal transport has been implicated as a pathogenic mechanism in a number of neurodegenerative diseases, including glaucoma. The long RGC axon, with its high metabolic demand and crucial role in conveying neurotrophic signals, relies heavily on intact axonal transport. In this mini review, we consider the evidence for transport disruption along R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 58 publications
1
42
0
1
Order By: Relevance
“…It should be noted that CWS have been documented in several astronauts following LDSF. 1,5 As these are also seen following terrestrial radiation therapy 45 their presentation in astronauts following LDSF suggests [46][47][48][49][50][51][52][53][54] the possible role of space radiation exposure. 5 NASA is attempting to tease apart the role that each of these elements may play in SANS.…”
Section: Oct and Sansmentioning
confidence: 99%
“…It should be noted that CWS have been documented in several astronauts following LDSF. 1,5 As these are also seen following terrestrial radiation therapy 45 their presentation in astronauts following LDSF suggests [46][47][48][49][50][51][52][53][54] the possible role of space radiation exposure. 5 NASA is attempting to tease apart the role that each of these elements may play in SANS.…”
Section: Oct and Sansmentioning
confidence: 99%
“…In this model, OHT results in Wallerian-like degeneration53, which culminates in RGC death2652. In fact, previous studies have shown that part of the surviving RGC population after one week of OHT exhibits impaired retrograde axonal transport, supporting evidence that not all RGCs die immediately upon impaired axonal transport2526.…”
Section: Discussionmentioning
confidence: 76%
“…Increasing evidence indicates that functional deficits in axonal transport and neuronal signaling characterize early stages of glaucoma (Crish et al, 2010;Takihara et al, 2013;Dengler-Crish et al, 2014;Chen et al, 2015;Fahy et al, 2016) similarly to early pathologies of many chronic neurodegenerative conditions (Stokin, 2005;Conforti et al, 2007;Yoshiyama et al, 2007;Adalbert et al, 2009;Brady and Morfini, 2010). Given the slow progression of glaucomatous vision loss in humans, identification of early steps in the pathology can reveal potential targets for stopping or reversing the subsequent visual deficits.…”
Section: Discussionmentioning
confidence: 99%